The anti-policy of European anti-smuggling as a site of contestation in the Mediterranean migration 'crisis'. Issue 12 (10th September 2019) - Perkowski, Nina; Squire, Vicki
ABSTRACT: This article analyses the European anti-smuggling agenda as an anti-policy that derives legitimacy from fighting 'bad things', in terms that mask political disagreement. By juxtaposing the agenda to the experiences and understandings of those whom such measures affect most directly – people migrating without authorisation to the EU – it uncovers the productivity of anti-smuggling and the political contestations surrounding it. Based on a qualitative analysis of 257 interviews carried out with 271 people who travelled – or sought to travel – across the Mediterranean Sea by boat using smuggling networks, the article highlights the complicity of governing authorities and officials with smuggling networks and practices, as well as the diversity and ambivalences of relationships between smugglers and the smuggled. Going further, the article points to the specific ways in which anti-smuggling is contested by those on the move, which expose a central political disagreement over the legitimacy of mobility across borders.